Association between the Korean Triage and Acuity Scale level and severity of children with dyspnea in the emergency department - Kwansoo Han; Eui-Soon Kim; Young Min Oh; Yeon Young Kyong; Kiwook Kim; Hyun Ho Jeong; Jung Taek Park; Joo Suk Oh; Se Min Choi; Kyoung Ho Choi (Pediatric Emergency Medicine Journal, 2022)
Purpose Triage tools play a vital role in classifying the severity of children in emergency departments (EDs). We investigated the association between the Korean Triage and Acuity Scale (KTAS) and severity of dyspnea in the ED. Methods We conducted a retrospective study of children aged 3-14 years with dyspnea who visited the ED from January 2015 through December 2021. They were divided into severe (KTAS level 1-3) and non-severe (KTAS level 4-5) groups. Between the groups, we compared the clinical characteristics, including age, sex, associated symptoms, vital signs, route of visit, treatment at ED, and outcomes. Results Among a total of 468 children with dyspnea, 267 and 201 were assigned to the severe and non-severe groups, respectively. The severe group had higher frequencies of fever (21.7% vs. 13.9%; P = 0.031), cough (53.2% vs. 43.3%; P = 0.034), systemic steroids (42.3% vs. 25.9%; P < 0.001), intravenous fluids (47.6% vs. 25.4%; P < 0.001), oxygen therapy (16.5% vs. 6.5%; P = 0.001), inotropics (4.1% vs. 1.0%; P = 0.042), and hospitalization (24.7% vs. 11.9%; P = 0.002). The severe group also showed a higher mean heart rate, respiratory rate, and temperature, and lower mean oxygen saturation (all Ps < 0.001). Among these findings, fever, heart rate, respiratory rate, temperature, intravenous fluids, oxygen therapy, inotropics, and hospitalization remained significantly different between the groups after defining the severe group as a KTAS level 1-2. Conclusion This study shows the association between KTAS and severity of dyspnea in the ED. Therefore, KTAS may reflect not only the initial clinical conditions but also emergency measures and outcomes in children with dyspnea who visit EDs.